2014
DOI: 10.2147/jir.s54360
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein and exercise-induced changes in subjects suspected of coronary artery disease

Abstract: BackgroundInflammation plays a major role in the development of atherosclerosis. We wanted to investigate the effects of exercise on high-sensitivity (hs) C-reactive protein (CRP) in subjects who were suspected of having coronary artery disease (CAD).MethodsBlood samples were obtained before, 5 minutes after, and 20 hours after an exercise test in 155 subjects who were suspected of CAD. Coronary anatomy was evaluated by computed tomography coronary angiography and/or coronary angiography.ResultsMedian baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In this direction, different epidemiologic studies have revealed that specific SNPs in the different genes such as IL-6, 13 , 16 18 IL-17, 19 IL-18, 20 and IL-23 are associated with the development of CAD. 21 27 In the present study, a significant association between the CAD GG carriers of rs1946518 and rs187238 SNPs and the higher circulating IL-8 levels was shown. In contrast, their respective heterozygote carriers (TG and GC) showed a significant association with lower IL-6 and IL-8 levels.…”
Section: Discussionsupporting
confidence: 60%
“…In this direction, different epidemiologic studies have revealed that specific SNPs in the different genes such as IL-6, 13 , 16 18 IL-17, 19 IL-18, 20 and IL-23 are associated with the development of CAD. 21 27 In the present study, a significant association between the CAD GG carriers of rs1946518 and rs187238 SNPs and the higher circulating IL-8 levels was shown. In contrast, their respective heterozygote carriers (TG and GC) showed a significant association with lower IL-6 and IL-8 levels.…”
Section: Discussionsupporting
confidence: 60%
“…Evidence exists showing exercise increases hsCRP up to 24-h post exercise, but this is in individuals who have performed very strenuous physical activities such as running marathons. 87 In a cohort of patients with coronary artery disease, Mouridsen et al 39 found that hsCRP increased in the first 5 min following a moderate exercise test, but that this increase was attenuated at 20-h. 39 These results indicate that exercise could cause unwanted variation in post intervention hsCRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…37 Finally, baseline hsCRP may be elevated in patients who have recently experienced a cardiac event, 38 and post exercise levels of hsCRP may be elevated in the period directly following intense exercise. 39 …”
Section: Introductionmentioning
confidence: 99%
“…Study in subjects suspected of coronary artery disease, a symptom-limited exercise stress test induced increase in CRP significantly. The results indicate that the exercise has potential to cause unwanted variations of CRP (Mouridsen et al 2014).…”
Section: Discussionmentioning
confidence: 92%